Analysis of the Meaning of Da'aa in the Interpretation of Ibn Kathir and As-Sa'di with the Approach of Wujuh wa al-Nadhoir and Toshihiko Izutsu's Semantics - Muhammad Fatih Kanzul Akrom; Mahfud Mahmudi; Muhammad Fatkhur Rasyid; Abdullah Yusuf Mushthofa; Fayiz Yan Avicena (Bulletin of Islamic Research, 2023)
This study aims to examine the interpretation of da'wah verses in the Qur'an that contain the word “دعا” (pray, call, call out). The word “دعا” has a broad meaning in the Qur'an, including the call to pray to Allah as a form of worship and obedience. Using the approaches of comparative tafsir, wujuh wan nadhoir, and toshihiko izutsu semantics, this study identifies and analyzes relevant verses, as well as tracing the interpretations of classical and contemporary scholars regarding the use of the word “دعا”. The results show that the word “دعا” not only describes supplication and hope to Allah, but also includes deep spiritual aspects in the context of da'wah. Prayer in these verses serves as a means of communication with Allah, confirmation of faith, and as a call for good and a warning against evil. This study highlights the importance of understanding the meaning of supplication in da'wah to increase the effectiveness of the message conveyed and strengthen the spiritual connection with Allah. This study also shows that the interpretation of da'wah verses that use the word “دعا” provides comprehensive guidance for Muslims to be more solemn in every prayer.